Lärande och omsorg som process eller resultat? Förskolan möter näringslivets verksamhetsstyrning - Lindqvist, Beatriz (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2017)
The article discusses how elements from different logics juxtapose and interweave and shape preschool’s practice in different ways. Regulatory frameworks – such as the national curriculum, parental evaluation surveys or the municipal performance report – provide external norms, which can be reinforced or contested through the narratives and actions of the practitioners. The subject positions that are constructed are closely related to each other, but are represented by different characteristics and timelines. Learning activities emerge as a powerful concept that generates action and requires responsibility and progress, while caring activities seem to be reduced to represent nurture, routine and stagnation. Depending on formal education, nursery nurses (a two-year gymnasium education) are linked to the children’s immediate needs for attention and comfort while university-educated preschool teachers linked to children’s learning and future schooling. In the work team, they are expected to have a close and equal relationship with each other, under the premise of tacit approving the ranking between them and act complementarily. At first glance, the preschool seems to integrate and valorize equal educational and care-giving practice to support the development of children. However, this article points that the interplay of competing logics may have unwanted consequences that should be problematized. If both care and learning are seen as prerequisites for the development of all children, this purpose is counteracted by a polarization of the work team.